Cyprus : Ninth Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Waiver of Applicability of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Cyprus. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses the economic recovery of Cyprus. Although progress on the structural reform agenda has been modest, the economic recovery has continued to gain strength. A range of policies have been discussed to accelerate reductions in nonperforming loans to revive lending and boost growth. Discussions also stressed the need to lock in fiscal gains given still-high public debt, and avoid further delays in implementing structural reforms that are necessary to reinvigorate growth and create employment. Despite lingering vulnerabilities in the banking sector and implementation delays in structural conditionality, the macro economy of Cyprus continues to improve. The unemployment and inflation projections have been adjusted downward.